ANALISIS PENGARUH SELF-EFFICACY, LOCUS OF CONTROL DAN CONSCIENTIOUSNESS TERHADAP JOB-SATISFACTION DENGAN GOAL-COMMITMENT SEBAGAI VARIABEL PEMEDIASI - MARTHA HADIANI ANGGRAITA (STIE Atma Bhakti, 2016)
This study analyzes the effect of Self-Efficacy, Locus Of Control and Conscientiousness on Job-Satisfaction with Goal-Commitment as mediation variable. The samples of this research were 145 employees respondences at BPU Rosalia Indah. The sampling methodology uses non-probability sampling, while the technique uses convenience sampling. The data analysis uses SEM. The results of the analysis are: 1) At BPU Rosalia Indah Self-Efficacy, Locus of Control and Conscientiousness significant effect on the Goal Commitment and Job-Satisfaction; 2) At BPU Rosalia Indah, Goal-Commitment has a positive effect on Job Satisfaction; 3) At BPU Rosalia Indah ,Goal-Commitment mediates the effect of Self-Efficacy, Locus of Control and Conscientiousness on Job-Satisfaction. Key word: Self-Efficacy, Locus Of Control, Conscientiousness, Goal Commitment, Job Satisfaction.